Nông nghiệp ứng phó với biến đổi khí hậu - Tài liệu dùng cho cán bộ địa phương các cấp của Việt Nam - Luu NQ; Pham TS; Le DH; Le, Van Hai; Nguyen TTT; Vu HL; Ngo DM; Bui Tan Yen; Dinh TKD; Sebastian, Leocadio S. (2015)
Climate smart agriculture concepts and principles must be simplified for local government officials and other technical officer to be able to operationalize key elements into local development programs in Vietnam. Climate smart agriculture needs to be simplified and often demystified in order to enhance its wider up take at regional and local levels. The brochure is written in Vietnamese for the benefit local partners and technical persons who speak and read Vietnamese language only.